KEMAJUAN PENELITIAN DAN PUBLIKASI TENTANG KONSELING RELIGIUS: TINJAUAN DAN ANALISIS BIBLIOMETRIK - Harahap, Jumli Sabrial (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
Counseling services during the time of the Prophet Muhammad SAW are reflected in the hadith, showing him as an extraordinary counselor. The purpose of this study is to see and analyze the development of scientific papers published in Scopus regarding religious counseling. The research method uses a literature review, especially using bibliometrics. Data retrieval was obtained from the Scopus website using the keyword "Religious Counseling" obtained 3,006 articles. Data analysis using bibliometrics using Vosviewer software. The results of the study showed that in 2020 there were 36 articles and in 2024 there were 43 documents. The highest citation related to the document was the research results of Mintert, J., Tran, A.G.T.T., Kurpius, S. with 14 times. The name of the author who published the most articles was Asadzandi, M. with 6 documents. Document 89 has been published by the United States. Analysis of the title Spiritual, religious and counseling is widely used by the author. Co-authorship analysis has 15 co-authors. Analysis of the author's keywords is often used, namely 'Spiritual, religious and counseling. The development of scientific works on religious counseling is increasing and is widely published in international journals. The results of this study are expected to be utilized by further researchers, especially in related fields of science.